Oblique versus transverse anastomotic stricture in gastric pull up: an open-label controlled trial - Farahnak, Mohammad-Reza; Askarpour, Shahnam; Peyvasteh, Mehran; Sokouti, Mohsen; Feizi, Iraj (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : Survival in esophageal cancer can be improved by surgery. In the palliative surgery for esophageal cancer, the fundus is anastomosed to the esophageal remnant, which is routinely transverse after esophagectomy. Developing stricture at the anastomosis precludes recovery from dysphagia. One study on esophageal cancer showed that the occurrenceof stricture formation in transverse esophagogastric anastomosis was 13.6%. Due to high prevalence of stricture formation in transverse anastomosis, we introduced a new technique (oblique anastomosis) and compared it with routine transverse anastomosis in a prospective randomized clinical trial. Materials and methods : This clinical trial was carried out in Imam Hospital (Tabriz, Iran) between 2003 and 2008. Two hundred subjects with biopsy-proven esophageal cancer entered the study in two groups of equal size. All patients underwent transhiatal esophagectomy (THE) and gastric pull-up. Cervical esophagogastric anastomosis randomly constructed in a transverse (T) and oblique (O) manner was completed in the two groups. In addition, two-layer hand-sewn anastomosis was done in both groups.Similar suture materials were used: non-absorbable for the posterior layer and absorbable for the inner layer. Results: There were 117 males (58.5%) and 83 females (41.5%) with a mean age of 60.47 years (range, 28–81 years). In the six-month follow-up period, 25 (12.5%) patients had dysphagia [20 (20%) cases in group T vs. 5 (5%) cases in group O (p = 0.001, 95% CI: 0.076–0.586, OR = 0.211]. Nineteen cases (9.5%) had structural anastomotic strictures 16 (16%) cases in group T vs. 3 (3%) cases in group O (p = 0.002, 95% CI: 0.046–0.577, OR = 0.162). Conclusion : This study showed that stricture formation was significantly lower in oblique esophagogastric anastomosis in THE than transverse anastomosis. Oblique technique is recommended for anastomosis.